MATHEMATICS COMICS BASED ON PROBLEM-BASED LEARNING WITH ILLUSTRATIONS OF JAMBI CULTURE - Sastrawati, Eka; Maryono, Maryono; Budiono, Hendra; Destrinelli, Destrinelli; Yantoro, Yantoro (JURNAL EDUSCIENCE, 2025)
Purpose—This research is important to overcome the low interest of students in learning mathematics in elementary schools due to the conventional approach, which is less interesting. By developing comics based on Problem-Based Learning (PBL) that promote local Jambi culture, this research aims to create more interesting, contextual, and relevant learning and increase the interest of fifth-grade students in mathematics.Methodology- This research and development (R&D) approach uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), which was employed to design the mathematics comics. Data were collected through pre-test and post-tests, observations, interviews, questionnaires, and documentation. These comics were developed based on a needs analysis derived from teacher interviews and student feedback, focusing on integrating local cultural aspects, particularly the Gentala Arasy temple, to make the learning material more engaging and relevant. Conducted during the 2024/2025 academic year at SDN 151/IV Jambi City, this research involved 42 students from two selected classes.Findings- The findings indicate that the developed PBL-based comic media was feasible and effective in supporting mathematics learning. Including Jambi cultural illustrations proved valuable in increasing student engagement, motivation, and understanding of mathematical concepts. The comic's visual and narrative elements helped simplify abstract mathematical ideas, making them more accessible and comprehensible for elementary school students. Feedback from both experts and students affirmed the comics' validity, readability, and overall effectiveness in enhancing learning outcomes. This study demonstrates that culturally contextualized comic media can significantly improve students' interest and achievement in mathematics.Significance- The developed comics offer an innovative solution for mathematics education and contribute to the advancement of local culture-based educational tools, providing valuable resources for teachers and students in Jambi and other regions.Keywords: Problem-Based Learning, Mathematics comics, Ethnomathematics, Jambi Culture